THERAPY PROCESS IN APPROACH CONVENTIONAL AND ISLAM - Hidayat, Arifin Hidayat (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
Abstract                Humans who experience psychic disorders with various kinds of imbalances must be treated as a treatment to help individuals to their best condition. Therefore the therapeutic process is one of the ways to help the elderly individual from his life problems of course with the right approach, so that the process done has a positive impact on the individual. This study will lead us to an understanding of the therapeutic process with conventional and Islamic approaches.               The methodology used in this paper is literature study, namely by gathering information that is relevant to the topic or problem that is the object of research. In this case the books contain the conventional therapeutic process and the Islamic therapy process, so that they get valid information about the two approaches.               The findings of this study are as follows: The therapeutic process in a conventional approach, for example psychoanalytic theory in a basic concept of theory focuses on Id, ego, super ego and unconsciousness and awareness, according to this theory the processes used are: to participate in intellectual work. 2. Stimulate the counselee's ego to fight every demand for the id. 3. Restoring the counselee's ego by detecting the material and implusions that his mother had entered into unconsciousness.               While in Islamic therapy that has the view that humans are one of the most perfect creatures, both from the physical aspect, moreover spiritual. So when humans fall into the flow of defamation, the therapy can be used as follows: 1. Spiritual Exercise 2. Establish affection 3. The nature of the example 4. Good advice: gentle and true. 5. Reciting prayers     Keywords: Conventional Therapy, Islamic Therapy